Performance Evaluation of Tracking and Non-Tracking PV Systems in Scotland, UK - Kajiama, F. M.; Ngala, G. M.; Abdulkadir, M.; Fruh, W. G. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Solar energy is an important component of renewable energy resources. Solar tracking system is a suitable option that could be used in capturing both direct (beam) and diffuse radiation. To investigate the performance of tracking and non-tracking PV systems, solar angles were estimated based on solar geometry and combined with global and direct radiation measurement covering a year. Results showed that using horizontal fixed panels or tracking the sun about single axis was worst to boost the energy collection of the panels, while tracking the sun about two axes or using fixed but optimally tilted panels was found to be better and efficient. With an annual electricity of 67.3 and 66.3 kWh/h respectively and an improvement of 3.65 and 2.12%. This implies that fixed tilted panel will be suitable to be employed in the region with lower irradiance as Edinburgh.